Quorum Sensing: Not Just a Bridge Between Bacteria - Derun Liu; Yonglin Lu; Ziyun Li; Xin Pang; Xueyan Gao (MicrobiologyOpen)
ABSTRACT The study of quorum sensing (QS) has gained critical importance, offering insights into bacterial and microorganism communication. QS, regulated by autoinducers, synchronizes collective bacterial behaviors across diverse chemical signals and target genes. This review highlights innovative approaches to regulating QS, emphasizing the potential of quorum quenching and QS inhibitors to mitigate bacterial pathogenicity. These strategies have shown promise in aquaculture and plant resistance, disrupting QS pathways to combat infections. QS also provides opportunities for developing biosensors for early disease detection and preventing biofilm formation, which is critical to overcoming antimicrobial resistance. The applications of QS extend to cancer therapy, with targeted drug delivery systems utilizing QS mechanisms. Advancements in QS regulation, such as the use of nanomaterials, hydrogels, and microplastics, provide novel methods to modulate QS systems. This review explores the latest developments in QS, recognizing its significance in controlling bacterial behavior and its broad impacts on human health and disease management. Integrating these insights into therapeutic strategies and diagnostics represents a pivotal opportunity for medical progress.